Precocious Puberty A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
The parents of a 04-year-old girl bring her to a Gynaecologist because of breast development, appearance of pubic hair and periodic per vaginal bleeding. Her medical history is unremarkable. The parents are of average height, and the mother reports first menstruating when she was 11 years old. At physical examination, the girl is 100 cm tall , weighs 17 kg, and has a bodymass index of 17. Her pubertal development is classified as Tanner stage 3 breast development and Tanner stage 2 pubic hair development. She was diagnosed as a case of precocious puberity. Appearance of secondary sexual development before the age of 9 in a male child and before the age of 8 in a female child is called precocious puberty. When the cause of precocious puberty is premature activation of the hypothalamic-pituitary axis, it is called central or complete precocious puberty and she was a case of central precocious puberty. After proper consult she was treated by GnRHa suppressor of pituitary till 11 years of age.Bangladesh J Obstet Gynaecol, 2015; Vol. 30(2) : 109-112